2018
DOI: 10.1002/jcb.27189
|View full text |Cite
|
Sign up to set email alerts
|

miR‐129 targets CDK1 and iASPP to modulate Burkitt lymphoma cell proliferation in a TAp63‐dependent manner

Abstract: Burkitt lymphoma is one of the most common lymphatic system cancers with poor outcome in adult patients. p53-induced apoptosis is a critical signaling for preventing tumor development. Cyclin B/cyclin-dependent kinase 1 (CDK1) phosphorylates inhibitor of apoptosis stimulating protein of P53 (iASPP) to promote iASPP nucleus localization and its inhibitory effect on p53. However, p53 is frequently mutated in Burkitt lymphoma, which gains novel oncogenic properties. Recently, the p53 family member, p63, became an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Since TAp63α is expressed in some Burkitt lymphomas and diffuse large B cell lymphomas [ 79 , 80 ] and TAp63α over-expression inhibits lytic reactivation in NOKs-Akata cells, we asked whether TAp63α helps maintain EBV latency in a lymphoma cell line that expresses TAp63α. The level of TAp63α protein expression in various EBV-infected lymphoma cell lines or lymphoblastoid cell lines (including the ILB1 DLBCL line, the Akata BL cell line, an Akata EBV strain virus transformed lymphoblastoid cell line (LCL), and an AG876 EBV strain virus transformed LCL) was examined by immunoblot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since TAp63α is expressed in some Burkitt lymphomas and diffuse large B cell lymphomas [ 79 , 80 ] and TAp63α over-expression inhibits lytic reactivation in NOKs-Akata cells, we asked whether TAp63α helps maintain EBV latency in a lymphoma cell line that expresses TAp63α. The level of TAp63α protein expression in various EBV-infected lymphoma cell lines or lymphoblastoid cell lines (including the ILB1 DLBCL line, the Akata BL cell line, an Akata EBV strain virus transformed lymphoblastoid cell line (LCL), and an AG876 EBV strain virus transformed LCL) was examined by immunoblot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The ΔNp63α isoform is the primary isoform expressed in epithelial cells. Interestingly, TAp63α is expressed in some B-cell lymphomas, including Burkitt lymphoma and diffuse large B cell lymphomas (DLBCL), and is a potential marker for poor patient prognosis [42,55,[78][79][80][81]. ΔNp63α does not bind directly to the EBV immediate-early gene promoters or prevent R binding to the EBV genome.…”
Section: The C-terminal Domain Of Tap63 and δNp63 Inhibits R-induced Lytic Reactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that miR-129 can be developed into an effective therapeutic target for these types of cancer. In addition, multiple targets of miR-129 have been validated, including CDK1 and iASPP in Burkitt lymphoma,32 PAK5 in hepatocellular carcinoma,33 and MAL2 in papillary thyroid carcinoma 34. These studies suggested that miR-129 exhibited tissue-specific functions.…”
Section: Discussionmentioning
confidence: 97%
“…Most notably, the tumor suppressor miR-129 has been shown to suppress expression of CDK1 and iASPP through binding with their transcripts. Moreover, CDK1 targeting by miR-129 can lead to inhibition of iASPP phosphorylation, therefore deterring nuclear localization of iASPP and its suppressive impact on p53 and TAp63 [ 13 ].…”
Section: Cyclin-dependent Kinase 1 (Cdk1)mentioning
confidence: 99%